For life to happen: device and performativity in Asymptotes - Manata, Franz (Programa de Pós-Graduação em Artes Visuais - PPGAV/EBA/UFRJ, 2024)
The text presents an artistic experiment by Anna Costa e Silva, which evokes a term from analytical geometry - asymptotes - to talk about reverberations between different existences, which leap across the screen to transform us into agents and witnesses of time. Supported by the concepts of performativity (Dorothea von Hantelmann), device-cinema (André Parente, Antônio Fatorelli, Katia Maciel and Victa de Carvalho), establishment (Lisette Lagnado) and relational dimension (Nicola Bourriaud), I seek to analyze a type of work that is conceived as a place for maneuvers, a portal that generates activities, which relates to the here-and-now, so that "things" happen - the experience itself. A type of work that creates a dynamic between itself, the body and thought, which requires physical and mental participation. What I intend to demonstrate is that Anna Costa e Silva has been carrying out work that uses communicative processes to establish relationships in modes of socialization that seek to form subjects, bonds and identities, based on the investigation of different forms of human interaction, showing that what the artist does is place herself at the center of the problem and invite us into experiences that involve intimacy and strangeness, which, consequently, open space for life to happen.